2014
DOI: 10.1016/j.jacc.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Multicenter Evaluation of the Direct Flow Medical Transcatheter Aortic Valve

Abstract: The present study demonstrates the safety and efficacy of the DFM system in surgical high risk patients with severe aortic stenosis and complex anatomy aortic regurgitation was less than moderate in 99% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
78
4
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 13 publications
17
78
4
2
Order By: Relevance
“…69 Data from the multicenter prospective trial of the direct flow medical transcatheter aortic valve (DISCoVER CE) trial evaluating this valve reported 2.7% with major strokes, 16% with permanent pacemaker implantation, with 99% with absent or only mild aortic regurgitation. 69 These data are in line with the recent experience from the ACURATE TF study, 70 investigating the performance of the Symetis ACURATE valve (Symetis, Ecublens, Switzerland). The procedural success was high; 13% required a permanent pacemaker; and 95% had mild or absent perivalvular leak at 30 days after implantation.…”
Section: The Future: Better Results With Next-generation Tavi Devices?mentioning
confidence: 99%
“…69 Data from the multicenter prospective trial of the direct flow medical transcatheter aortic valve (DISCoVER CE) trial evaluating this valve reported 2.7% with major strokes, 16% with permanent pacemaker implantation, with 99% with absent or only mild aortic regurgitation. 69 These data are in line with the recent experience from the ACURATE TF study, 70 investigating the performance of the Symetis ACURATE valve (Symetis, Ecublens, Switzerland). The procedural success was high; 13% required a permanent pacemaker; and 95% had mild or absent perivalvular leak at 30 days after implantation.…”
Section: The Future: Better Results With Next-generation Tavi Devices?mentioning
confidence: 99%
“…The multicenter non-randomized DISCOVER trial in 100 patients with logistic EuroSCORE ≥20 or other high surgical risk features not reflected by the log EuroSCORE showed a 30-day survival rate of 99% and mild or no AR in 99% (73/74 patients). 45 Initially observed higher residual gradients after valve implantation were not significant in the DISCOVER trial because of a clear strategy that included repositioning of the valve in cases of significant residual stenosis. The mean echocardiographic gradient decreased from an average of 45.9±9.6 mmHg (n=72) to an average of 12.6±7.1 mmHg (n=72) post-procedure over 30 days.…”
Section: Direct Flow Medical Aortic Valvementioning
confidence: 98%
“…In the first study performed, aortic regurgitation was mild or less in 98.6% of patients. 20 Both the Lotus and Direct Flow Medical valves are commercially available in Europe but remain investigational in local and national U.S. research centers.…”
Section: The New Trial Valvesmentioning
confidence: 99%